An analysis on the farm productivity and rturns from bt cotton. A case study of coimbatore district - M, Subramani; S, Jagadeesh pand (Journal of Management and Science, 2013)
India has made impressive strides on the agricultural front during the past three decades. India is the leading producer in many of the agricultural crops including the commercial crops. Objectives of the study, To analyse the socio economics conditions of the Cotton farmers in the study area and study the cost of cultivation of Bt cotton farmers in the study area. Methodology of this study, in order to estimate the impact of BT cotton on existing cropping pattern in the district of Coimbatore, a survey was conducted in the rural areas of the district. A sample of 500 respondents was taken from the cotton growing villages of the district namely, Anaimalai, Annur, Karamadai, Kinathukadavu, Madukarai, Pollachi,Sarkarsamakulam and Sulur are the major blocks were BT cotton are grown. Important findings of the study, on the use of inputs in the cotton farm activity indicated that, for a majority of the inputs, the use of these inputs increases with the increase in the size of holdings and the reason put forth was that a majority of the sample growers particularly, the small, medium and large growers adopt mechanization in cotton farming which is the cause of higher usage of agricultural inputs. Suggested in this study, The low productivity added with the poor quality of the product results in poor for the product which ultimately results in poor returns. The higher share of expenditure incurred on pests and disease control and for the application of higher dose of chemical pesticides and labour intensive nature of cultivation are the probable reasons for high cost of production.